METHOD OF DEVELOPING A LINGUISTIC RESEARCH ALGORITHM - Amanbayeva, D.B.; Kudritskaya, M.I. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2020)
The article presents a step-by step approach to developing an algorithm for a linguistic research, taken as a part of English teachers’ professional training. Tips for building a research plan are given on the example of the project with the objective to find and analyze idioms in the songs of the group «Queen».
Keywords: algorithm for a linguistic research; English teachers’ professional training; research plan